2021
DOI: 10.3390/met11091357
|View full text |Cite
|
Sign up to set email alerts
|

Mg-Ca0.3 Electrochemical Activity Exposed to Hank’s Physiological Solution and Properties of Ag-Nano-Particles Deposits

Abstract: This work compares the degradation of Mg and Mg-Ca0.3 alloy when they are exposed for 14 days to Hank’s solution at 37 °C. A combination of immersion test, electrochemical techniques (PDP, EIS, EN), and surface characterization methods (SEM-EDS, XRD, and XPS) were carried out. The pH change over time, the lower mass loss (≈20%), and the lower concentration of the released Mg2+ ions (≈3.6 times), as well as the lower level of the surface degradation, allowed to consider the positive effect of Ca, presenting Mg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 163 publications
(212 reference statements)
0
2
0
Order By: Relevance
“…, Appendix A), electroless deposited on ZnO/Mg-Ca0.3, are observed at 2θ values of 38.18 • , 44.25 • , 64.72 • and 77.46 • , indexed for diffractions from the (111), (200), (220) and (311) planes, corresponding to the presence of Ag crystals of FCC cell structure (JCPDS No.04-0783). In our previous work, the Ag nanoparticles electroless deposited on Mg-Ca0.3 presented similar XRD spectra[45].…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…, Appendix A), electroless deposited on ZnO/Mg-Ca0.3, are observed at 2θ values of 38.18 • , 44.25 • , 64.72 • and 77.46 • , indexed for diffractions from the (111), (200), (220) and (311) planes, corresponding to the presence of Ag crystals of FCC cell structure (JCPDS No.04-0783). In our previous work, the Ag nanoparticles electroless deposited on Mg-Ca0.3 presented similar XRD spectra[45].…”
mentioning
confidence: 59%
“…The Ca 2+ ion and its compounds (phosphate type) can be tolerated (low toxicity) by the human body at relatively high levels of ~4 g/day. The Mg-Ca alloys are also mechanically compatible with bone, biodegradable and exhibit interesting characteristics as a potential material for implants, providing cell adhesion (osteoconductivity) and cell growth stimulation on the implant surface [44,45]. In a previous study, we reported the antibacterial effect of Ag-NPs electroless deposited on the Mg-Ca0.3 surfaces, with a percentage inhibition of diameter growth (PIDG) of up to 64% against E. coli and 83% against S. aureus [45].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 10 shows the equivalent electrical circuit used [31] to model the experimental impendance data, which includes, as the main components, the solution resistance (R s ), a constant phase element (CPE 1 ) and a resistor (R 1 ), associated with the double layer and charge transfer resistor (substrate/electrolyte interface) [42,43]. The (CPE 2 ) and the resistance (R 2 ) are characteristic of the corrosion process at the metal surface through the corrosion layer and the release of Mg ions.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…These devices are thought to provide adequate mechanical properties at the fracture site during new bone tissue healing before being replaced by natural tissue. Mg-based biomaterials have been the topic of comprehensive study over the last two decades [11][12][13][14]. However, the appropriateness of Mg alloys as a fracture fixation system has been questioned because of their low resistance to corrosion and relatively inferior mechanical properties.…”
Section: Introductionmentioning
confidence: 99%